2021
DOI: 10.25115/eea.v39i11.5853
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis on the Impact of External Auditing Quality on the Earnings Management of the Iraqi Industrial Companies under financial for the period 2010 to 2017

Abstract: This study intends to recognize the rate at which Earnings Management (EM) is practiced by Iraqi industrial organizations registered in the Iraq stock exchange and also to distinguish the most essential factors that influence the Earnings Management (EM) practices through the audit quality. This study also intended to distinguish the type of correlation between the characteristics of auditing quality. This study additionally aimed to distinguish the type of correlation between the characteristics of auditing q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The study found that most of the banks listed in the market practice Earnings Management. The study of (Rahman et al, 2021) aimed to analyze studies that dealt with Earnings Management for the period from 2017 to 2019. The study found that there is great agreement among most researchers that Earnings Management methods are used in order to mislead shareholders.…”
Section: Earnings Management In the Academic Literaturementioning
confidence: 99%
“…The study found that most of the banks listed in the market practice Earnings Management. The study of (Rahman et al, 2021) aimed to analyze studies that dealt with Earnings Management for the period from 2017 to 2019. The study found that there is great agreement among most researchers that Earnings Management methods are used in order to mislead shareholders.…”
Section: Earnings Management In the Academic Literaturementioning
confidence: 99%
“…(Rattray, 2020) believes that the internal auditing standards are "a binding performance model that specifies the general rules to be followed when carrying out the audit process or professional custom". The AICPA has defined auditing standards as "general guidelines that guide auditors to carry out their professional responsibilities in auditing financial statements" (Brown, 2020;Abdul Rahman et al, 2021). (Harahap, 2018) confirms that the generally accepted standards of internal auditing represent "a basis for the work of internal auditors, specifying their technical responsibilities and following up on their professional performance".…”
Section: The Concept Of Internal Auditing Standardsmentioning
confidence: 99%
“…The internal control system: includes the organizational plan, control, means of coordination, and supervision, so that no single person is responsible for all stages of the process, as each employee's work is subject to review by another employee who is involved in the process' implementation, and control work is characterized by contributing to the strengthening and strengthening of i. (Abdul Rahman et al, 2021).…”
Section: Dmentioning
confidence: 99%